Spontaneous Uterine Hematoma in a Cat - Kim, Kihoon; Kim, Junhyung; Woo, Heung-Myoung (Acta Scientiae Veterinariae, 2026)
Background: The current case report describes uterine hematoma in a cat. Hematomas are blood accumulation within tissues due to hemorrhage. Although, the precise etiology of uterine hematoma is difficult to determine in animals, uterine hemorrhages are believed to be in association with the estrus cycle or cystic endometrial hyperplasia-pyometra complex induced by progesterone. In humans, uterine hematomas in association with abortion and premature delivery are occasionally reported. Clinical signs include abdominal distension, increased water uptake, and anorexia according to the previous literature. The recommended treatment for the uterine hematoma is ovariohysterectomy in veterinary medicine. To the authors’ knowledge, there are only two reported cases of uterine hematoma in the veterinary literature, one in a dog and another in a mare and this is the first reported case of a spontaneous uterine hematoma in a cat. Case: A 10-year-old female Persian cat presented with a few-weeks history of anorexia and lethargy. On history taking from the owner, there was no history of trauma or injury. On physical examination, a skin mass between the 3rd and 4th mammary gland in the right caudal abdomen was identified. A complete blood count was unremarkable. On serum chemistry analysis, an increased blood urea nitrogen was identified. Coagulation panels including activated partial thromboplastin time (APTT) and prothrombin time (PT) were within the normal range. Ultrasonography revealed a well-defined mass around the right uterine horn and computed tomographic examination showed a non-contrast-enhancing mass connected to the right uterine horn. Since neoplasia was not completely ruled out, ovariohysterectomy with removal of the mass followed by the right unilateral mastectomy was performed. On gross examination, there was no fluid within the uterus. Subsequently, the uterine was submitted for cytologic examination, revealing no inflammatory cells or bacteria. Histologically, the mass of the abdominal skin was ductular adenoma. The uterine mass histology was consistent with a blood clot with fibrins, indicating hematoma, and there were no signs of significant inflammation or neoplasia. The patient was healthy and had a good appetite on the 1st postoperative day; however, the cat died on day 7 due to acute renal failure, which was assumed to result from preoperative condition of the cat. However, the precise reason of the death could not be identified because necropsy was declined by the owner. Based on the history from the owner, blood examination findings, and gross appearance of both thickened uterine horns, extensive hemorrhage during the last estrus was suspected to be the cause of uterine hematoma. Since this is the 1st case report describing spontaneous hematoma in the uterine, the hematoma should be considered as a differential diagnosis of the uterine mass. Discussion: In humans, uterine hematoma frequently complicates pregnancy, especially in the 1st trimester of gestation. A large intramural uterine hematoma in association pregnancy has been also reported. Compared to humans, uterine hematoma is extremely rare in veterinary medicine. There are only 2 reported cases of uterine hematoma including 1 in a dog and another in a mare. Although the exact etiology of uterine hematoma in animals is unclear, it is assumed that uterine hematoma is associated with uterine hemorrhage or iatrogenic damage. In the case reported here, there was no evidence suggestive of trauma or recent abdominal surgery. Moreover, considering coagulation panels within the normal range, coagulation diseases were also excluded. Massive local extravasation of erythrocytes during a recent estrus cycle has been proposed as an etiology of uterine hematoma. In the present case, based on the history from the owner, blood examination findings, and gross appearance of both thickened uterine horns, extensive hemorrhage during the last estrus was suspected to be the cause of uterine hematoma. However, the exact etiology remains unclear. The recommended treatment for the uterine hematoma is ovariohysterectomy in veterinary medicine. Although the number of cases is insufficient, the metastasis of the mammary gland tumor to the various organs including inguinal lymph nodes, uterus, lungs, heart, muscle, or urinary bladder has been reported previously. In the case reported here, since the skin mass was identified between the right 3rd and 4th mammary gland in addition to the mass within the right uterine horn, metastasis was not completely ruled out. Thus, the right unilateral mastectomy was performed in addition to the ovariohysterectomy. However, considering the mammary gland tumor was identified as benign ductular adenoma by histopathologic evaluation, the uterine lesion was assumed to be unrelated to the mammary gland tumor. Keywords: cat, ovariohysterectomy, uterine hematoma, uterine hemorrhage, uterus.